2018
DOI: 10.1007/s10456-018-9627-4
|View full text |Cite
|
Sign up to set email alerts
|

IGF2 and IGF1R identified as novel tip cell genes in primary microvascular endothelial cell monolayers

Abstract: Tip cells, the leading cells of angiogenic sprouts, were identified in cultures of human umbilical vein endothelial cells (HUVECs) by using CD34 as a marker. Here, we show that tip cells are also present in primary human microvascular endothelial cells (hMVECs), a more relevant endothelial cell type for angiogenesis. By means of flow cytometry, immunocytochemistry, and qPCR, it is shown that endothelial cell cultures contain a dynamic population of CD34+ cells with many hallmarks of tip cells, including filopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 56 publications
(83 reference statements)
5
34
0
Order By: Relevance
“…In our previous study, we found that IGF2 mRNA is enriched in CD34 + tip cells as compared to non-tip cells, and that knockdown of IGF2 gene expression by siRNA leads to a reduction in the fraction of tip cells in endothelial cell cultures, and in reduced sprouting from spheroids [2]. Now, we verified this finding in a novel 3D angiogenesis model [34] after knockdown of IGF2 by siRNA.…”
Section: Sprouting Angiogenesis In Vitro Is Dependent On Igf2 and Is supporting
confidence: 75%
See 3 more Smart Citations
“…In our previous study, we found that IGF2 mRNA is enriched in CD34 + tip cells as compared to non-tip cells, and that knockdown of IGF2 gene expression by siRNA leads to a reduction in the fraction of tip cells in endothelial cell cultures, and in reduced sprouting from spheroids [2]. Now, we verified this finding in a novel 3D angiogenesis model [34] after knockdown of IGF2 by siRNA.…”
Section: Sprouting Angiogenesis In Vitro Is Dependent On Igf2 and Is supporting
confidence: 75%
“…Previously, we have shown that knockdown of IGF1R reduces sprouting in vitro [2]. When studying the other receptors of the IGF family, we found that knockdown of INSR significantly decreased the number of sprout per spheroid but not their length, whereas knockdown of IGF2R did not change the number or length of sprouts ( Fig.…”
Section: Inhibition Of Insr But Not Inhibition Of Igf2r Reduces Sprmentioning
confidence: 59%
See 2 more Smart Citations
“…It enables spread of tumor cells to distant sites and formation of metastasis and tumor progression. Angiogenesis is a complex multistep process that includes proliferation of endothelial cells, degradation of extracellular matrix (ECM), migration of endothelial cells through remodeled ECM and tube formation by endothelial cells (Dallinga et al, 2018;Sato, 2004). MetAP2 has been shown to play an important role in endothelial cell proliferation (Ehlers et al, 2016;Sato, 2004).…”
Section: Antitumor Activity Of Nitroxolinementioning
confidence: 99%